The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/pip.2885
|View full text |Cite
|
Sign up to set email alerts
|

On the role of solar photovoltaics in global energy transition scenarios

Abstract: The global energy system has to be transformed towards high levels of sustainability in order to comply with the COP21 agreement. Solar photovoltaic (PV) offers excellent characteristics to play a major role in this energy transition. The key objective of this work is to investigate the role of PV in the global energy transition based on respective scenarios and a newly introduced energy transition model developed by the authors. A progressive group of energy transition scenarios present results of a fast grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
143
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 275 publications
(147 citation statements)
references
References 32 publications
(65 reference statements)
3
143
0
1
Order By: Relevance
“…The hourly modelling results in a more accurate system description, highlights flexibility, and presents a synergy effect of various power generation and storage technologies required to be installed to attain a fully RE-based power system. The model has been used before to conduct studies for several different regions so far, and a detailed description can be found in [38][39][40][41]. For this analysis, the integration of desalination and non-energetic industrial gas demand was not included.…”
Section: Model Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The hourly modelling results in a more accurate system description, highlights flexibility, and presents a synergy effect of various power generation and storage technologies required to be installed to attain a fully RE-based power system. The model has been used before to conduct studies for several different regions so far, and a detailed description can be found in [38][39][40][41]. For this analysis, the integration of desalination and non-energetic industrial gas demand was not included.…”
Section: Model Overviewmentioning
confidence: 99%
“…PV offers economic solutions in regions with already high but also low electrification rates for new capacity additions and for meeting demands on-grid and off-grid [17,35]. Recent studies have explored the possibility of 100% RE based power systems in different countries and regions [38][39][40][41]. Barasa et al [40] described a 100% RE energy system for SSA, covering the electricity demand of the sectors power, water desalination and industrial gas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, there are no further installations in wind power plants after 2030. This result documents the outstanding impact of low cost solar PV supported by low cost battery storage that lead to a solar PV electricity generation share of 79%, which is significantly higher than the average of about 40% found in the global average assumptions for the year 2030 [25], but also higher than the 48% solar PV share for the MENA region [66]. However, comparable results had been found already earlier for the case of Israel [30], where the solar PV share had be found for cost optimized systems to about 90% of the total electricity supply.…”
Section: Discussionmentioning
confidence: 75%
“…This system eliminates the reliance of SWRO desalination plants on non-renewable fossil fuels and concerns about greenhouse gas emissions. Meanwhile, reflecting the Saudi government's vision of high renewable energy capacities, there is recent literature that discusses the 100% renewable energy transition of different countries and regions [25][26][27][28][29][30][31][32], as well as detailed visualization of respective electricity systems [33].…”
Section: Introductionmentioning
confidence: 99%